Gravity: Where Do We Stand? 2015
DOI: 10.1007/978-3-319-20224-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Lorentz Breaking Effective Field Theory Models for Matter and Gravity: Theory and Observational Constraints

Abstract: A number of different approaches to quantum gravity are at least partly phenomenologically characterized by their treatment of Lorentz symmetry, in particular whether the symmetry is exact or modified/broken at the smallest scales. For example, string theory generally preserves Lorentz symmetry while analog gravity and Lifshitz models break it at microscopic scales. In models with broken Lorentz symmetry there are a vast number of constraints on departures from Lorentz invariance that can be established with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 195 publications
(332 reference statements)
1
11
0
Order By: Relevance
“…Given the the latters can be reduced to mSME constraints, we shall here discuss specifically only the first kind (one can find a discussion of the second kind in e.g. [120]).…”
Section: Constraints On Einstein-aether Gravitymentioning
confidence: 99%
“…Given the the latters can be reduced to mSME constraints, we shall here discuss specifically only the first kind (one can find a discussion of the second kind in e.g. [120]).…”
Section: Constraints On Einstein-aether Gravitymentioning
confidence: 99%
“…On the other hand, in general relativity one solves the analogous problem of comparing tangent spaces at the different spacetime points by using the tetrad e a µ (x) that maps all these spaces into one 'ambient' Minkowski space: 4 . We made use of the same trick in constructing our free action (36).…”
Section: Spacetime and Relative Localitymentioning
confidence: 99%
“…These were the motivations that served as a launching pad for two major research projects: one positing abandoning the Lorentz invariance, leading to construction of models with Lorentz Invariance Violation (LIV) (see [3][4][5] for a review); and the second, known under the name of Doubly (or Deformed) Special Relativity (DSR), in which much milder alternation of the Poincaré symmetry was posed. In both cases it was implicitly understood that deviations from the standard symmetries of special relativity are of the quantum gravity origin, although the explicit relation relations between the two was never understood in a satisfactory way.…”
Section: Introductionmentioning
confidence: 99%
“…While we have shown that the Lorentzian metric structure can emerge as an effective property of the gravity sector at long distances, it is phenomenologically important to ensure that not only the Lorentzian signature but also the Lorentz symmetry can emerge in the matter sector at long distances [18]. For the emergence of Lorentzian signature in the matter sector, we thus need to couple the matter sector to derivatives of the clock field as in [7].…”
Section: Discussionmentioning
confidence: 99%